The education index in the context of sustainability: Thermo-economic considerations - Grisolia, Giulia; Fino, Debora; Lucia, Umberto (Frontiers in Physics, 2022)
Sustainable development requires new technical solutions to be realised, due to the new approach to production, consumption, and management of resources. These technologies require also technical skills from workers, and citizens. These technical abilities are mostly based on the knowledge of mathematics and sciences, acquired during the schooling years. In this paper, we develop a thermo-economic analysis of the sustainable development in relation to the needs of mathematical and technical skills of the future workers. To do so, the Education Index is considered in order to improve it towards a measure of the technical abilities of the young people, maintaining its present social meaning of preventing child exploitation. The result is an improvement of the Thermodynamic Human Development Index, by introducing the OECD-PISA assessment, in order to allow the decision makers to analyse their policies, based on a more comprehensive vision of the present, to better design the future. Finally, we point out the need to focus public policies on the continuous stimulus of intellectual reasoning and on problem-solving based education to develop the processing capacity and foster the creative capabilities of the younger population that builds the backbone of the future workforce.